Oral manifestation and management of food hypersensitivity reaction in children: a case report: Manifestasi oral dan penatalaksanaan reaksi hipersensitif terhadap makanan pada anak: laporan kasus - I Gusti Ngurah Putra Dermawan; I Nyoman Gede Juwita Putra (Makassar Dental Journal, 2022)
Introduction: Food hypersensitivity reaction is a reaction that harms the body to food or food additives whose reactions can be mediated through two different mechanisms, immunological and non-immunological. Objective: This article reports on case and management of hypersensitivity reactions to food. Case: A 10-year-old girl came with thrush on the tongue for 3 days ago, sore and painful; previously consumed traditional fried snack. Ulcerated lesions, multiple, shallow, sunken base with yellowish color surrounded by an erythematous margin on the anterior of the tongue. Total IgE examination was 535.6 IU/mL from the range 0-387 IU/mL. The diagnosis leads to allergic stomatitis. The patient was instructed to apply a tongue compress with hyalu-ronic acid 0.025% mouthrinse then apply triamcinolone acetonide 0.1% in orabase 3 times a day and multivitamin. Conclusion: Knowing the oral clinical signs of this reaction can determine the appropriate treatment plan in handling similar cases, especially in children.